Az induktív módszer a bibliai héber nyelv tanításában - EGERESI, László Sándor (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2026)
The Inductive Method in the Teaching of Biblical Hebrew. Teachers of Biblical Hebrew are following and using the standard grammar books and workbooks of their field. We use the theoretical books of Gesenius and Joüon’s work (revisited by late Muraoka) and several practical books from Weingreen, Jenni, Seow, Lettinga, and Neef, to but a few. The common ground of these practical grammars are their deductive method, but we know there are some alternative ways as well. Such an alternative way is the inductive method, which is also well known from William Sanford LaSor’s grammar Handbook of Biblical Hebrew – An Inductive Approach Based on the Hebrew Text of Esther (Grand Rapids: Eerdmans, 1989 – first print: 1978). The method has several advantages and disadvantages, as the author himself provided a useful overview of this issue[1]. The inductive approach in teaching classical languages is said to be innovated and first used by the American scholar W. R. Harper (1856–1906). Besides his Hebrew grammar, Harper also wrote a Greek and Latin grammars, and even the phrase “inductive method” is used in the title of these grammars. The Hebrew grammar was published in 1881 and went through six subsequent editions over a period of thirty-five years, attesting to its popularity as a workbook. However, a hitherto unknown Hebrew grammar written by the Hungarian scholar István Tamaskó (1801–1881) had already employed this method in academic circles. The inductive grammar was written in 1841, so it predates Harper’s work by several decades. The article at hand aims to explore the possible European roots of the inductive method used by a Hungarian scholar. The origins and antecedents of Tamaskó’s book remain unknown and require further research. [1] LaSor, William Sanford (1974): The Inductive Method of Teaching Hebrew – Its Advantages and Its Pitfalls, In: Hebrew Abstracts. 15. 108–119.